Search for QCD-instanton induced events in deep inelastic ep scattering at HERA - Chekanov, S; Derrick, M; Krakauer, D; Loizides, J; Magill, S; Miglioranzi, S; Musgrave, B; Repond, J; Yoshida, R; Mattingly, M; Antonioli, P; Bari, G; et al. (2004)
A search for QCD-instanton-induced events in deep inelastic ep scattering has been performed with the ZEUS detector at the HERA collider, using data corresponding to an integrated luminosity of 38 pb-1. A kinematic range defined by cuts on the photon virtuality, Q2 > 120 GeV 2, and on the Bjorken scaling variable, x > 10-3, has been investigated. The QCD-instanton induced events were modelled by the Monte Carlo generator QCDINS. A background-independent, conservative 95% confidence level upper limit for the instanton cross section of 26 pb is obtained, to be compared with the theoretically expected value of 8.9pb.